Alexander of Aphrodisias as an interpreter of the Aristotelian noetics - Boeri, Marcelo D. (Estudios de Filosofía, 2012)
this essay intends to show that, despite the relevance of Alexander’s interpretation of Aristotle’s agent intellect (the intellect that Alexander indentifies with god), such an interpretation cannot be right due to reasons of systematic order that go against some basic Aristotelian premisses, both ontological in general and noetical and psychological in particular. In the development of his essay, Boeri highlights some arguments and explanations provided by Pseudo Philoponus, who (rightly according to him) is concerned with encompassing the issue of the intellect on the psychological side, which presupposes that the intellect must have a bodily support. A consequence of this examination, Boeri suggests (i) that not only Alexander’s interpretation of intellect does not constitute a correct exegesis of Aristotle’s De anima III 5, but that (ii), when identifying the agent intellect with the intellect “coming from without”, with god, and with the first cause, Alexander introduces an important incoherence within his own psychological conception, which acknowledges Aristotle’s thesis that the psychological states “exist” through the body.